Antecedents, Dimensions, and Outcomes of Gastronomy Experience in Tourism: A Systematic Literature Review - Mar'atul Fahimah; Nanang Suryadi; Raditha Dwi Vata Hapsari (MARGIN ECO, 2026)
Gastronomy experience has become an important construct in tourism studies because food increasingly shapes destination image, tourist satisfaction, memorable experiences, and future travel intention. However, existing studies remain fragmented in terms of terminology, measurement dimensions, antecedent factors, behavioral outcomes, and research contexts. This study aims to systematically synthesize the literature on gastronomy experience in tourism by examining four main aspects: antecedents, experience dimensions, outcomes, and emerging research contexts. A systematic literature review was conducted using the PRISMA approach. The literature search was carried out through the Scopus database and supplemented by manual searches of relevant peer-reviewed journal articles published between 2021 and 2025. After the screening and eligibility process, 48 articles were included in the final review and analyzed using thematic synthesis. The findings show that gastronomy experience is shaped by authenticity, sensory quality, service quality, tourist involvement, social interaction, destination context, and digital mediation. The most frequently identified dimensions are authenticity, memorability, sensory-aesthetic quality, affective response, hospitality/social interaction, novelty, and cognitive-cultural learning. The review further indicates that gastronomy experience contributes to tourist satisfaction, destination image, loyalty, revisit intention, advocacy, willingness to pay, and travel intention. The main contribution of this article is an integrative framework that links antecedents, experience dimensions, mediators/moderators, and behavioral outcomes. This framework clarifies gastronomy experience as a multidimensional construct connecting food consumption, destination value creation, and future tourist mobility.